Strategi Pengembangan Usaha Lebah Madu Kelompok Tani Mau Sigaro Hutan Kemasyarakatan Desa Gamsungi Kabupaten Halmahera Barat - Nur Hikmah; Aqshan S Nurdin; Laswi Irmayanti; Meylinda Y Hanafi (Fakultas Kehutanan, Universitas Hasanuddin, 2020)
The purpose of this study was to determine the activity of Mau Sigaro farmer group in Gamsungi village and identified internal and external factors that became the strengths, weakness, opportunities, and threats of the honey bee cultivation business, in order to find a good strategy to develop it using SWOT matrix. The result of SWOT analysis showed the strength point was consisted of professional human resorces, received capital assistance, produced a pure honey, and short marketing channel. The weakness of this farmer group was limited opportunity for all the member to join some workshop related to honey bee cultivation, needed more capital assistance to pay the maintenance expense, the price of the product was cheap, using manual technic, and none market promotion. The opportunities identified as the support from the government to the farmer group and it had gained consumer trust towards the product. The threats was found as weather exchange, it had not used technology to gain information, and it still did not have a permanent marketing partner to distribute the product. Alternative stategy can be used to develope the honey bee business based on SWOT result is Mau Sigaro farmer group needs to gain more relation with the government and marketing partner, increase the number of production and the quality of the product, send the member to join honey bee cultivation workshop, using the newest technology in honey bee cultivation and mass communication to spread the product information, and using an attractive packaging to gain more consumers. Key words: honey bee cultivation, farmer group, developing strategy, SWOT